2005
DOI: 10.1080/10739680590934817
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Peripheral Arterial Disease: Sustained Impairment of Nutritive Microcirculation and Its Recovery by Chronic Electrical Stimulation

Abstract: Femoral artery ligation following iliac ligation impairs arteriolar vasodilator capacity, capillary perfusion, and shear-dependent function of microcirculatory endothelium more than iliac ligation alone and is more representative of long-standing ischemia in PAD. Chronic intermittent electrical stimulation can normalize these derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Other studies (34,56) have shown that perfusion subsequent to femoral artery occlusion is not correlated with capillarity. Studies have shown that chronic reductions in flow and pressure can result in enhanced constriction and inward remodeling characterized by wall thinning (1,6,8,17,19,41,49,50,64,67), characteristics that occur in human critical limb ischemia (17)(18)(19). Thus, the profound decrease in distal microvascular flow and pressure could result in similar decompensatory events in the precapillary arterioles and small arteries that control the majority of microvascular resistance (3,27,42,77).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (34,56) have shown that perfusion subsequent to femoral artery occlusion is not correlated with capillarity. Studies have shown that chronic reductions in flow and pressure can result in enhanced constriction and inward remodeling characterized by wall thinning (1,6,8,17,19,41,49,50,64,67), characteristics that occur in human critical limb ischemia (17)(18)(19). Thus, the profound decrease in distal microvascular flow and pressure could result in similar decompensatory events in the precapillary arterioles and small arteries that control the majority of microvascular resistance (3,27,42,77).…”
Section: Discussionmentioning
confidence: 99%
“…1). 3,9,14,20,27,30,[38][39][40]42,59,62 This threedimensional model is used in calculations of blood flow and oxygen distributions. However, due to the complexity of the system and the number of the parameters that are of physiological interest, we choose a twodimensional cross section of the tissue (400 · 208 lm 3 , boxed in Fig.…”
Section: Anatomymentioning
confidence: 99%
“…51 In addition, average capillary blood velocity is higher in rats that have undergone exercise training. 3 Thus, using empirical relationships for viscosity and hematocrit distribution, 25,46 and experimental measurements of blood oxygenation and velocity in ligated rat EDL 3,16,17,44,46 we simulated blood flow for perfused tissue and partially perfused tissue (where only half of the tissue arterioles have blood flow).…”
Section: Blood Flowmentioning
confidence: 99%
See 2 more Smart Citations